2017
DOI: 10.3389/fpls.2017.00149
|View full text |Cite
|
Sign up to set email alerts
|

DkPK Genes Promote Natural Deastringency in C-PCNA Persimmon by Up-regulating DkPDC and DkADH Expression

Abstract: The astringency of Chinese pollination-constant non-astringent (C-PCNA) persimmon (Diospyros kaki Thunb.) can be naturally removed on the tree. This process is controlled by a single locus and is dominant against other types of persimmons; therefore, this variant is an important candidate for commercial cultivation and the breeding of PCNA cultivars. In our previous study, six full-length coding sequences (CDS) for pyruvate kinase genes (DkPK1-6) were isolated, and DkPK1 is thought to be involved in the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…2). This finding is consistent with the previous reports that the high expression of the genes PDC , PK, ERF , and LAR promote the deastringency of persimmon fruits [35, 36]. It should be noted that these genes exhibited a similar pattern (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…2). This finding is consistent with the previous reports that the high expression of the genes PDC , PK, ERF , and LAR promote the deastringency of persimmon fruits [35, 36]. It should be noted that these genes exhibited a similar pattern (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We found that DkMYB19 could interact with the DkPK2 protein, which is a pyruvate kinase that may be involved in the natural loss of astringency in C-PCNA persimmon mediated by the upregulation of DkPDC (pyruvate decarboxylase) and alcohol dehydrogenase ( DkADH ) expression during the last developmental stage ( Guan et al, 2016 , 2017 ). The pGBDT7–DkMYB19 and pGADT7–DkPK2 fusion proteins were co-transformed, and the Y2H assay verified the interactions ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 96%
“…We found DkMYB19 could interact with a DkPK2 protein, that is a pyruvate kinase gene maybe a potential roles in the natural loss of astringency in C-PCNA persimmon via the up-regulation of DkPDC and DkADH expression during the last developmental stage (Guan et al ., 2016, 2017). The pGBDT7-DkMYB19 and pGADT7-DkPK2 fusion protein were co-transformed to the Y2H furthermore verified the interactions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DkMYB6 was identificated as a putative transcriptional activator, induced by high CO2, which is involved in persimmon fruit deastringency, by operating on both DkPDC structural genes and DkERF transcription factors (Fang et al ., 2016). Meanwhile, pyruvate kinase genes ( DkPK ) are involved in the natural loss of astringency in Chinese PCNA persimmon via enhancement of the transcript levels of the DkPDC and DkADH genes (Guan et al ., 2016; 2017). Furthermore, Xu et al .…”
Section: Introductionmentioning
confidence: 99%